A Curriculum for whom? Rereading ’Implementing the Australian Curriculum in Rural, Regional, Remote and Distance-Education Schools’ from a Rural Standpoint. - Roberts, Philip (Australian and International Journal of Rural Education, 2017)
This paper builds upon the evolving methodological perspective of a rural standpoint (Roberts, 2014b), and its related method of strategic eclecticism (Roberts & Green, 2013), to reanalyse existing data behind a previously published paper by Drummond, Halsey and van Breda (2012). It does this through an examination of the role of the rural in the Australian curriculum, drawing upon work that raises the lack of recognition of rurality in the curriculum as an important social justice issue (Roberts, 2014a; Roberts, 2015; Roberts & Downes, 2016). Through the reanalysis the paper illustrates that the rural educators who responded to the initial study had a concern for local places, and a perspective that an Australian Curriculum has the potential to marginalise local knowledges, and rural and remote schools more generally. Furthermore the re-analysis shows that age, time teaching in a rural or remote setting, distance from a major centre and jurisdiction of the school all influence respondents views in distinct ways. Consequently this paper illustrates the utility of re-analysing previous research reports, the use of a rural standpoint in research, and that rural educators have specific rural-related concerns regarding the Australian Curriculum that are largely unaddressed.